Distribution of herbicide‐resistant acetyl‐coenzyme A carboxylase alleles in Lolium rigidum across grain cropping areas of South Australia. (30th September 2013) - Malone, J M; Boutsalis, P; Baker, J; Preston, C; Novak, Stephen
Summary Resistance to the acetyl‐coenzyme A carboxylase (ACCase)‐inhibiting herbicides in Lolium rigidum is widespread in grain cropping areas of South Australia. To better understand the occurrence and spread of resistance to these herbicides and how it has changed with time, the carboxyl transferase (CT) domain of the ACCase gene from resistant L. rigidum plants, collected from both random surveys of the mid‐north of Southern Australia over 10 years as well as stratified surveys in individual fields, was sequenced and target site mutations characterised. Amino acid substitutions occurring as a consequence of these target site mutations, at seven positions in the ACCase gene previously correlated with herbicide resistance, were identified in c. 80% of resistant individuals, indicating target site mutation is a common mechanism of resistance in L. rigidum to this herbicide mode of action. Individuals containing multiple amino acid substitutions (two, and in two cases, three substitutions) were also found. Substitutions at position 2041 occurred at the highest frequency in all years of the large area survey, while substitutions at position 2078 were most common in the single farm analysis. This study has shown that target site mutations leading to amino acid substitutions in ACCase of L. rigidum are widespread across South Australia and that these mutations have likely evolved independently in different locations. The results indicate that seed movement, both within and between fields, may contribute to the spread of resistance in a single field. However, over a large area, the independent appearance and selection of target site mutations conferring resistance through herbicide use is the most important factor.